Beginning SharePoint with Excel - Courter, Gini (Apress, 2012)
This book is intended for IT professionals and for business users who see the benefits of electronic collaboration and want to maximize the tools they already have available. Most books of this type are written for programmers and require a high level of technical knowledge. Because there’s so much you can do with SharePoint and Excel without programming, we intentionally excluded techniques and solutions that require programming. Our intention was to make this book accessible to those high-end users who aren’t programmers but who, with the right level of knowledge, can still make a big difference in solving business problems in their organizations. In other words, even if you don’t know the difference between XML, SQL, and .NET, you can create powerful team collaboration solutions with SharePoint and Excel.